Garbo - Gottlieb, Robert 1931-2023 (Farrar, Straus and Giroux, 2021)
"Award-winning master critic Robert Gottlieb takes a singular and multifaceted look at the life of silver screen legend Greta Garbo, and the culture that worshiped her"--
Keywords: Garbo, Greta -- 1905-1990; Garbo, Greta / 1905-1990; Garbo, Greta / 1905-1990 / Influence; Motion picture actors and actresses / Sweden / Biography; Motion picture actors and actresses / United States / Biography; Motion pictures / History / 20th century; PERFORMING ARTS / Film / History & Criticism; BIOGRAPHY & AUTOBIOGRAPHY / Entertainment & Performing Arts; BIOGRAPHY & AUTOBIOGRAPHY / Women; Influence (Literary, artistic, etc.); Motion picture actors and actresses; Motion pictures; Sweden; United States; 1900-1999; Biographies; History; Biografie